2012
DOI: 10.1093/ejcts/ezr221
|View full text |Cite
|
Sign up to set email alerts
|

Early and late failure of tissue-engineered pulmonary valve conduits used for right ventricular outflow tract reconstruction in patients with congenital heart disease

Abstract: Compared with the other conduit for RVOTR Matrix conduits showed a high incidence of failure. Our results suggest that the use of Matrix conduits for RVOTR should be considered with caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 22 publications
1
53
0
1
Order By: Relevance
“…52 A larger trial with decellularized porcine valves in 93 patients showed freedom from conduit failure to be 60% at 24 months and below 25% after 36 months. 53 In this study by Perri et al, there was no single cause of failure, but histology showed the presence of inflammatory giant cells in the explanted valves. While immune compatibility of decellularized native valves can potentially be resolved, another challenge with tissue valves in pediatric patients is the elevated risk of ECM degradation and calcification.…”
Section: Discussionmentioning
confidence: 56%
“…52 A larger trial with decellularized porcine valves in 93 patients showed freedom from conduit failure to be 60% at 24 months and below 25% after 36 months. 53 In this study by Perri et al, there was no single cause of failure, but histology showed the presence of inflammatory giant cells in the explanted valves. While immune compatibility of decellularized native valves can potentially be resolved, another challenge with tissue valves in pediatric patients is the elevated risk of ECM degradation and calcification.…”
Section: Discussionmentioning
confidence: 56%
“…[26][27][28] Later reports on the performance of these valves were, however, variable. [29][30][31] Cicha et al 32 reported on four adolescent patients implanted with Matrix P valves, who were reoperated due to early to midterm graft failure (12-15 months). The explanted valves showed massive inflammatory and fibrotic responses at the distal region, lumen narrowing, and low recolonization of the decellularized matrix.…”
Section: Introductionmentioning
confidence: 99%
“…SV, stroke volume. authors show promising results at 3 years follow-up, 2 others report high early conduit failure rate 1,3 making the pursuit for the ideal TEHV conduit especially for children and young adults paramount. Decellularized TEHVs based on biodegradable synthetic materials may serve as suitable replacement of allografts and xenografts, but preclinical study in nonhuman primate and ovine models are characterized by valvular regurgitation due to leaflet shortening and reduced leaflet coaptation.…”
Section: Discussionmentioning
confidence: 99%
“…Xenografts and human cryopreserved valves are characterized by increased early reintervention rates due to strong immunological reactions with subsequent calcification. [1][2][3] The lack of growth potential also predisposes children to recurrent surgeries thus increasing morbidity. Decellularized allograft heart valves have been used as tissue-engineered heart valve (TEHV) scaffolds by several investigators with promising results, 4,5 however, little is known about the cellular mechanisms underlying neotissue formation in these TEHVs.…”
mentioning
confidence: 99%